The effectiveness of using the strategy of concept maps on the level of achievement and attitudes of students of the Department of Physical Education in the subject of teaching methods (Journal of the College of Basic Education, 2023)
Concept maps play a major role in the educational process, as they contribute to focusing the attention of the curriculum designer on teaching concepts and on planning curricular activities that serve as a tool for learning the concept. The concept map, which includes a wide range of related concepts, becomes the cognitive component of the curriculum, and the curriculum becomes a chain of intended learning outcomes.The study aims to: Identify the effectiveness of using the concept map in academic achievement in the subject of teaching methods among students in the Department of Physical Education.This study was conducted on a sample of students from the Department of Physical Education in the College of Basic Education. The results of the research were:Teaching using the strategy of concept maps is better than teaching in the traditional "usual" way with regard to practical and theoretical achievement and the trend towards the subject of teaching methods.The researcher recommends the need to use the strategy of concept maps in learning teaching methods by faculty members at the College of Basic Education, Department of Physical Education, as one of the effective methods of learning, which leads to the achievement of many desired goals.